Design of the power distribution system of building H05 in Musheireb Downtown, Doha, Qatar - Aguiman, Jose Jeoffrey T. (Manila Professional Regulation Commission, 2014)
The purpose of this report is to present and design the electrical Power Distribution System of Building HOS, commercial, residential under the area of Musheireb Downtown where manage and developed by Government Agency Musheireb Property, Doha, State of Qatar. In this study, Building HOS supplied power coming from a two 3-phase 11kV, HV, transformer power substation prepared by Musheireb or Doha land Substation incoming source going to 3-phase, 16kV/llkVA, transformer, 41S volt as TX-H-1, TX-H-2, TXH-3 is connected to low voltage switchgear which feed the main distribution board, sub main distribution board down to distribution board to each respective load of the building. This technical report shall involve substantial calculation such as load calculations and each layout plan with respect to load schedule, transformer size determination, wires and cables sizing, protective devices and short circuit calculation. The related references books which utilized articles in this technical report are based on applicable codes, regulation and standard used International and locally in the State of Qatar and International. So carefully recommended as part of conclusion in this report were in should be enumerated to impart evaluation observation as a result of the real technical reason of this report.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-670G donated by Mr. Jaime E. Mendoza.
Keywords: Buildings -- Electric equipment